MODERNIZING OF JAVANESE WOMEN DRESSING STYLE CULTURE IN 20TH CENTURY: THE EDUCATION IMPACT - Moch. Dimas Galuh Mahardika (Universitas Sebelas Maret, 2022)
The Dutch colonialism not only leaves stories about exploitation, the breakdown of social strata, and other inhumane stories. On the other hand, the presence of Dutch colonialism in Nusantara gives the influence of modern culture to several aspects of bumiputra people's lives. After the colonization runs for centuries in Nusantara, the colonial government seems to have the awareness for